Image authentication and restoration using watermarking - Lwin Mar Soe. (2009)
Copyright protection of images has become a major concern with the rapid expansion of the Internet, which contains millions of freely available images. Digital watermarking is a way to preserve such information against intentional proof. In this project, the original image is watermarked (some information is hidden in the document) so that if it is modified, it can be detected since the watermark gets disturbed. Not only that, the modified portion may be corrected such that the original image information at that part may be restored. Thus, authentication and restoration of image is possible against third party modifications. One of the watermarking techniques, which are based on the discrete cosine transform, is tested by using Matlab programming and the results are analyzed.